Purna Man Chitrakar (1864 - 1939 AD): A Pioneer - Least Celebrated - Chitrakar, Madan (SIRJANĀ – A Journal Of Arts and Art Education, 2018)
A frequent debate or an issue favorite amongst the art-history buffs is usually found around when and who first used oil paints as a medium of painting and introduced photography in Nepal. On many occasions, the credits were attributed to a legendary name – Bhaju Man Chitrakar or Bhaju-macha. But it appears now many of those narratives were made more based on the popular hearsays rather than actual study of his oeuvre of works or a credible analysis of the circumstances then. The essay here seeks to analyze the roles of the prominent artists then – spanning late 80s of the 19th century to the late 30s of the 20th century. It is found the role played by a least celebrated artist Purna Man Chitrakar, seemed more credible – in ushering a new era, described as ‘Pre-modern’, with the irrefutable accounts of his workings in oil colors and photography. Moreover, his mentorship of many of the junior artists later proved momentous – leading to create different new streams in the evolution of Nepali Art – later.